Optimalisasi Pelayanan Publik melalui Komunikasi Efektif: Fokus Pemberdayaan Aparatur Desa di Desa Nanggerang Kabupaten Sukabumi - Zulmasyhur, Zulmasyhur; Setiawan, Heru Dian; Petrus L.W, Nicolaus (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2024)
This service focuses on Optimizing Public Services Through Effective Communication: Focus on Empowering Village Apparatus in Nanggerang Village, Sukabumi Regency. Meanwhile, the method adopted in this service is descriptive qualitative by providing understanding to explore information in the field with critical analysis according to the substance discussed. Two data collection methods were carried out to obtain the information needed for this service. First, primary data was obtained through observation activities, direct interviews with related parties, and the collection of related documents in the field. Second, secondary data was obtained through document analysis, especially reports produced by the Nanggerang Village Government. The results describe that the importance of communication in building public services can be a reference so that what is expressed to the public can be understood well and logically. Besides that, in the context of public communication theory, indicators such as knowledge, skills, and attitude are the basis for achieving public communication goals. Knowledge emphasizes the importance of paying attention to each individual's opinion, while skills are used to understand society's needs more deeply. Meanwhile, attitude ensures that the messages are addressed well to the public and conveyed clearly. With consistency in implementing these indicators, it is hoped that Nanggerang Village can achieve responsive, effective, and efficient public.